Perancangan Gedung Olah Raga dan Wisma Atlet dengan Pendekatan Biohilic Arsitektur - Nabila Puteri Islami; Sri Kurniasih; Tri Endangsih (MAESTRO, 2023)
Sport is one of the activities that is very popular with many people who have gone worldwide and become an integral part of people's daily lives. Sports activities can be a way to get away from the boredom and mental stress of daily routines. Sports are also useful to restore and refresh the body and soul as well as provide pleasure. The Ball Game Sports Building and the Cilegon Athlete's House is a sports venue that provides various types of indoor sports and a home for athletes in Cilegon City with a Biophilic Architecture approach. Visitors besides exercising can also have recreation, gather and enjoy the atmosphere in one area. The existence of the Ball Game Sports Building and the Cilegon Athlete's House can be an alternative for urban sports and recreation facilities which are currently lacking. The Sports Building has the potential to become a new icon for people who like to exercise in Cilegon City and its surroundings. The design of the Ball Game Sports Building and the Cilegon Athlete's House is directed more towards fulfilling facilities and is expected to become a place that can support and accommodate the development of the world of sports which has now become the lifestyle of many people in Indonesia. Keywords: Sports Building, Biophilic Architecture, Cilegon City